Principals' Facilities Maintenance Measures and Administrative Effectiveness in Private Secondary Schools in Kwara State, Nigeria - Olaifa, Adeseko Sunday; Ali, Mariam Adetola Arogundade; OLAIFA, Ebunlomo Oreoluwa; OLADIMEJI, Rasheedat Modupe; AKPALA, Kingsley Chigozie (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2024)
Maintaining physical infrastructure in private secondary schools is particularly critical because these institutions operate in a highly competitive environment where their reputation is tied to academic performance and the quality of their facilities. This study investigated the relationship between principals' facilities maintenance measures and administrative effectiveness in private secondary schools in Kwara State, Nigeria. The study was guided by two research questions and four research hypotheses. The descriptive survey of the correlational type was adopted for the study. The population of this study comprised 7,869 senior secondary school teachers. A sample of 250 teachers was selected using purposive and simple random sampling techniques. A researcher-designed instrument titled